2021
DOI: 10.11124/jbies-21-00194
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation after medical assistance in dying: a scoping review protocol

Abstract: Objective:This scoping review will collate and summarize the current literature on what is known worldwide about organ donation following medical assistance in dying. The information gathered will be used to inform updates of current and future policies on organ donation following medical assistance in dying in Canada.Introduction:Medical assistance in dying is a controversial and contentious issue worldwide. While more countries are legalizing medical assistance in this regard, very few allow organ donation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0
12

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 14 publications
0
35
0
12
Order By: Relevance
“…Originally, in our research protocol, 11 we presented an overarching research question (What processes, procedures, and outcomes have been reported in the literature worldwide about organ donation following MAiD? ), followed by 6 subquestions.…”
Section: Review Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, in our research protocol, 11 we presented an overarching research question (What processes, procedures, and outcomes have been reported in the literature worldwide about organ donation following MAiD? ), followed by 6 subquestions.…”
Section: Review Questionsmentioning
confidence: 99%
“…), followed by 6 subquestions. In this second part of the 2-part review, we address 2 subquestions, with the remaining questions addressed in a separate paper 12 . This second part addressed the following subquestions: What processes need to be in place for organ donation following MAiD? What are the specific procedures followed for organ donation following MAiD in the different settings? …”
Section: Review Questionsmentioning
confidence: 99%
“…In our research protocol, 15 we presented an overarching research question (What processes, procedures, and outcomes have been reported in the literature worldwide about organ donation following MAiD? ), which was followed by 6 subquestions.…”
Section: Review Questionsmentioning
confidence: 99%
“…We have included visual aids and detailed explanations of the different pathways used worldwide for organ donation processes following MAiD: the steps for organ donation following MAiD in the hospital setting; MAiD at the patient's home with organ retrieval in the hospital; and MAiD starting at home with completion in the hospital setting, followed by organ retrieval. 12 We have also examined the processes of organ donation following MAiD from the viewpoint of the health care professionals involved in the processes, and procedures around the potential benefits and challenges of the practice. Next, we explored insights into the roles and perceptions of health care providers during organ donation following MAiD, acknowledging the emotional weight carried by these professionals.…”
mentioning
confidence: 99%
“…Finally, the crucial role of clinical practice tools, and the need for education and support for health care providers involved in this juncture are explored. 12 This 2-part review offers a comprehensive foundation to guide further exploration of the existing evidence and, as mentioned, provides the basis for future initiatives in this field that require navigation of a complex blend of ethics, legality, and health care practices of organ donation following MAiD in our society. In a world where medical ethics are in constant flux and where compassion for others propels change, the boundaries of what is possible and acceptable are continuously pushed.…”
mentioning
confidence: 99%